The role of the company secretary in facilitating board effectiveness: reporting and compliance. (15th March 2020) - Nowland, John; Chapple, Larelle; Johnston, Joseph
Abstract: This study investigates how company secretaries (CS) influence board practices and financial reporting. All public companies have a secretary and this position may be combined with Chief Financial Officer (CFO) or legal counsel. Examining the period 2004–2015, we find that joint CS/CFOs hold more audit committee meetings, are associated with less earnings management and a greater likelihood of a clean audit opinion. Companies with joint CS/legal counsels are more timely filers and company secretaries of multiple companies schedule fewer committee meetings. These results indicate that company secretaries significantly influence board practices and financial reporting, depending on their role and busyness.